Preferred Tone of Nutrition Text Messages for Young Adults: Focus Group Testing - Pollard, C.; Howat, P.; Pratt, I.; Boushey, C.; Delp, E.; Kerr, Deborah (2016)
BACKGROUND: Young adults are a particularly hard to reach group using conventional health promotion practices as they do not see nutrition messages as personally relevant to them. Text messaging (short message service, SMS) offers an innovative approach to reaching young adults to support and promote dietary behavior change. OBJECTIVE: The aim of this study was to develop and test tonal preferences for nutrition text messages among young adults using focus groups. METHODS: A total of 39 young adults aged 18-30 years residing in Perth, Western Australia participated in four focus groups. Participants briefly discussed their perception of healthy eating and their responses to messages about increasing fruit and vegetables, and reducing "junk food" and alcohol intake. They ranked their preference for 15 nutrition messages across 3 dietary behaviors (fruit and vegetables, junk food, and alcohol) with 5 different message tones (authoritative, empathetic, generation Y, solutions, and substitutions) and identified the messages most likely to persuade young adults to change their diet. A 5-point ranking of the nutrition messages was from the most likely to least likely to persuade (1-5). The focus groups were conducted by a trained facilitator and observer and were recorded. Data driven content analysis was used to explore themes. Tonal preferences and potential motivators were collated and frequencies presented. RESULTS: Participants ranked offering substitutes (29%, 11/39) and using empathy (22%, 9/39) as the most persuasive message techniques in improving diets of young adults, with low responses for Generation Y (17%, 7/39), solutions (17%, 7/39), and authoritative (15%, 6/39) tones. Females were more likely to consider substitution messages persuasive (35%, 7/20) compared with males (22%, 4/19). A greater proportion of males compared with females considered authoritative messages persuasive: (22%, 4/19) compared with (7%, 1/20). There is a strong preference for a substitution tone for fruit and vegetable messages (52%, 20/39), and no overall message tone preference for junk food and alcohol messages. Substitutions were viewed as helpful and practical. Empathy was liked as it acknowledged previous efforts. Responses to authoritative tone were mixed with some feeling guilt while others found them informative. Acceptability of the solutions depended on the behavioral change and acceptability of the solution proposed. Generation Y tone had some support for junk food and alcohol messages, and if favored, was considered casual, humorous, catchy, and motivational. CONCLUSIONS: Substitutions and tone of empathy were favored as the most likely execution styles to motivate nutrition behavior change across all participants. There is no "one size fits all" with different tones preferred by individuals for different dietary behaviors. Although text messaging provides instant message delivery direct to the individual, these results demonstrate the complexity of developing motivational nutrition message for young adults. These findings reveal the importance of considering the tone and content and pretesting messages for health promotion text message interventions.